Inculcation of values across the school curriculum: development and validation of teachers’ orientation scale - Sahari, Mohammad; Mohd Sultan, Abdul Aziz; Raffor, Mohd Tahrim; Sheikh Ahmad, Ismail; Hj Zainuddin, Ahmad Marzuki; Abdul Rahman, Zainurin; Tunku Ahmad, Tunku Badariah; Rais, Haniza (IIUM Press, 1999)
Teacher orientation to the inculcation of values across school curriculum – a function of the teacher knowledge and attitudes – has been conceptualized as his or her (1) identification with the goals of the curriculum, and (2) conformity with the predetermined instructional behaviours. Based on this framework, the study explored the construct of teacher orientation to the inculcation of values across schools subject. More specifically, the study examined the likelihood of two underlying dimensions explaining the presence of variability in teacher orientation and the reliability of the dimensions. Using a 15-item instrument developed earlier for a descriptive inquiry, the present study measured and analysed responses from 103 secondary school teachers from two randomly selected schools. To arrive at the conclusions, the study applied principal component analysis and Cronbach’s alpha procedures. The results suggested that teacher orientation to value inculcation is a multidimensional construct. The more reliable dimensions of Teacher Orientation were found o be goal identification, conformity to planning tasks, and conformity to delivery tasks. The results add new information to, and may serve as a guide for future research in this area.